Slavic Question in Public Discourse of Russia in 1860s and 1870s (Materials from Newspaper “Novoe Vremya”) - O. O. Zavyalova (Научный диалог)
This article analyzes materials from the political and literary newspaper “Novoe Vremya” from the late 1860s to the early 1870s, reflecting issues of Slavic solidarity and the attitudes of its editors-publishers, A.K. Kirkor and N.N. Yumotov, towards national movements in Slavic territories, the popular idea of Pan-Slavism, and its Russian variant. Special attention is given to the concept of “new Pan-Slavism,” which emerged within the pages of “Novoe Vremya” during this period and proposed the creation of a union of equal Slavic nations — a Slavic federation led by the Russian Empire. In accordance with the theoretical and methodological framework of this study, particular emphasis is placed on the role of “Novoe Vremya” in the public discussions surrounding the Slavic question, which demonstrated a desire for national consolidation among the educated Russian society through the intellectual construction of Russian and Slavic identities. The conclusion drawn is that the editorial team of “Novoe Vremya,” advocating for the transcendence of Russian religious nationalism, developed ideas that foreshadowed the later movement of Neo-Slavism, which recognized the equality of Orthodoxy and Catholicism within the Slavic world and supported the independent development of each Slavic nation alongside a mutual respect for cultural dialogue.